Impact of Acid-Reducing Agents on Sotorasib Pharmacokinetics and Potential Mitigation of the Impact by Coadministration With an Acidic Beverage - Cardona, Panli; Strydom, Natasha; Houk, Brett (Clinical pharmacology in drug development, 2025)
Sotorasib exhibits pH-dependent solubility, making it susceptible to altered exposures when coadministered with acid-reducing agents (ARAs). Several clinical studies were conducted to investigate the impact of ARAs on sotorasib pharmacokinetics under different clinically relevant scenarios and to identify potential mitigation strategies. Upon coadministration of 960 mg of sotorasib and 40 mg of omeprazole under fasted conditions, sotorasib area under the concentration-time curve (AUC) and maximum observed plasma concentration (C ) decreased approximately 42% and 57%, respectively. Following coadministration with 40 mg of famotidine under fed conditions, sotorasib AUC and C decreased approximately 38% and 35%, respectively. The coadministration of sotorasib and 40 mg of omeprazole under fed conditions led to a 57% and 65% decrease in sotorasib AUC and C , respectively. When sotorasib was coadministered with omeprazole and an acidic beverage compared to sotorasib alone, AUC and C decreased approximately 23% and 32%, respectively, leading to a 19.0 percentage-point increase in AUC and a 24.6 percentage-point increase in C for sotorasib when compared to coadministration of sotorasib with omeprazole under fasted conditions. Sotorasib exposure decreased when coadministered with proton pump inhibitors and H receptor antagonists. Coadministration with an acidic beverage increased sotorasib exposure upon concomitant administration with omeprazole, which may represent a clinically attractive method to allow ARA use with sotorasib.